2020
DOI: 10.1039/d0cb00045k
|View full text |Cite|
|
Sign up to set email alerts
|

Glycosylated cyclophellitol-derived activity-based probes and inhibitors for cellulases

Abstract: New cyclophellitol-derived activity-based probes enable the sensitive detection and identification of cellulases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…As an initial test of specificity, we compared activity towards 4MU-GG and 4-methylumbelliferyl xylobioside (4MU-Xyl2), finding no detectable activity towards 4MU-Xyl2 among LsGH5_5A and TlGH12A, and a strong preferential activity towards 4MU-Xyl2 for LsGH10A (Additional file 11 : Table S2). Using 4MU-GG as substrate, we measured inhibition of LsGH5_5A, LsGH10A, and TlGH12A over time by glucosyl-β(1,4)-cyclophellitol [ 36 ] (GGcyc) at inhibitor concentrations as high as 50 μM under optimal buffer conditions (see Additional file 11 : Figs. S13 and S14 for effects of buffer and pH on enzyme activity).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As an initial test of specificity, we compared activity towards 4MU-GG and 4-methylumbelliferyl xylobioside (4MU-Xyl2), finding no detectable activity towards 4MU-Xyl2 among LsGH5_5A and TlGH12A, and a strong preferential activity towards 4MU-Xyl2 for LsGH10A (Additional file 11 : Table S2). Using 4MU-GG as substrate, we measured inhibition of LsGH5_5A, LsGH10A, and TlGH12A over time by glucosyl-β(1,4)-cyclophellitol [ 36 ] (GGcyc) at inhibitor concentrations as high as 50 μM under optimal buffer conditions (see Additional file 11 : Figs. S13 and S14 for effects of buffer and pH on enzyme activity).…”
Section: Resultsmentioning
confidence: 99%
“…ABP-Xyn, an established N -alkyl aziridine probe bearing a Cy5 + tag, was used to label endo -β-xylanases [ 35 ]. Endo -β-glucanase probe CB644 was prepared through click modification of ABP-Cel with Cy3 + alkyne in place of previously reported Cy5 + alkyne [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 28 32 More recently, we expanded the methodology toward retaining endoglycosidases in our work on xylobiose-configured ABPs to investigate endo -acting xylanases in Aspergillus secretomes. 33 , 34 Here, we reveal the efficacy of retaining glycosidase ABPP by the design and chemical synthesis of a panel of maltobiose epi -cyclophellitol derived retaining α-amylase inhibitors and ABPs, the kinetic and structural analysis of their interactions with microbial α-amylases, and the application of these probes for rapid detection and identification of α-amylases in fungal secretomes, mouse tissue, and human saliva. Our work complements a recent 24 study by Withers and colleagues, who reported a chemoenzymatic synthesis of maltobiose epi -cyclophellitol, to which we could match our chemically derived material and as well our structural work on α-amylase-inhibitor complexes.…”
Section: Introductionmentioning
confidence: 99%